Pioneer communities: collective actors in deep mediatisation. (September 2016) - Hepp, Andreas
The aim of this article is to draw attention to the phenomenon of media-related pioneer communities. The maker, quantified-self and open data movements have made clear how much an analysis of such pioneer communities can contribute to our understanding of changes in media and communication, together with related social and cultural changes. Pioneer communities do not only possess a marked sense of mission; they also develop ideas of media-related change that can provide orientation for broader social discourses. Studying pioneer communities as intermediaries between the development and the appropriation of new media technologies permits us to grasp current mediatisation processes from the actor's point of view without the need to first ascribe to them any unifying media logic. Pioneer communities are significant collective actors in the process of 'deep mediatisation' – the far-reaching entanglement of media technologies with the everyday practices of our social world.